Valuation of Mobile Spectrum to be Reassigned - Yunjeong Jang; Seungkeun Park; Kiwon Kim; Yongkyu Kim (International Telecommunications Society (ITS), 2024)
Recently, many countries have been reassigning the mobile communication spectrum and determining their price. In South Korea, the mobile communication spectrum was reassigned in 2021 with a usage period from 2022 to 2026. This study focuses on the methods for calculating reassignment fee. We aimed to measure the value of the spectrum by combining production function approach and engineering approach. First, we estimated the Cobb-Douglas production function and derived the price per spectrum unit using the equal marginal principle. Then, we assessed the appropriateness of this price through a DCF (Discounted Cash Flow) analysis. Next, considering that the value of spectrum varies by band according to their radio wave characteristics, we derived the value of each spectrum band from an investment perspective. We applied each band's relative weight to the per-unit spectrum price obtained earlier to determine each spectrum band's value. The estimation results indicated that the reassignment fee in 2021 was somewhat high in terms of total and band-specific prices. This study might give some insights to regulators facing spectrum reassignment.
Keywords: 330; Spectrum value; Spectrum reassignment fee; Cobb Douglas production function; Discounted cash flow(DCF); Engineering method